CURRENT RATIO DAN DEBT TO EQUITY RATIO PADA KINERJA KEUANGAN: BUKTI DARI PERUSAHAAN SUB SEKTOR KOSMETIK DAN KEPERLUAN RUMAH TANGGA - Rosdiana (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2023)
The purpose of this study was to determine the effect of the Current Ratio and Debt To Equity Ratio on Financial Performance in cosmetics and household goods sub-sector companies on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. The research sample consisted of 30 data. Data collection with documentation and data processing with t test, f test, and test the coefficient of determination of multiple linear regression using the classical assumption test. The results of the study show that the Current Ratio has no effect on financial performance. Meanwhile, the Debt to equity ratio has an effect on financial performance.